2019
DOI: 10.1097/md.0000000000017210
|View full text |Cite
|
Sign up to set email alerts
|

Gait turning patterns in chronic ischemic stroke males and its relationship to recovery

Abstract: Introduction:Impaired turning patterns have been considered as 1 factor which potentially leads to disability in chronic stroke patients. Mobility comprises 80% of the chief disability, and would eventually lead to falls. Expanded Timed Up and Go (ETUG) is an effective mobility assessment method. It utilizes video recording to analyze the conventional Time Up and Go (TUG) Test components, which includes turning pattern analysis.Methods:Six healthy males without stroke history and 21 chronic ischemic stroke mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The three-step turn is made to avoid the occurrence of overly wide rotation, and does not utilize pivoting, which was generally adapted in stroke patients with weaker balance on one side. 10 It was previously shown that unstable turn might follow up to unstable gait, being unable to walk in a straight line as the subject tries to restore their balance following the pivot turn. 9,10 In an extensive observation of turns, it was shown that young subjects with no difficulty of turning that none would initiate their turn with forward leaning, it would either be vertically aligned trunk and hip, slight backward lean, or initiated by lower extremity before being followed up by trunk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three-step turn is made to avoid the occurrence of overly wide rotation, and does not utilize pivoting, which was generally adapted in stroke patients with weaker balance on one side. 10 It was previously shown that unstable turn might follow up to unstable gait, being unable to walk in a straight line as the subject tries to restore their balance following the pivot turn. 9,10 In an extensive observation of turns, it was shown that young subjects with no difficulty of turning that none would initiate their turn with forward leaning, it would either be vertically aligned trunk and hip, slight backward lean, or initiated by lower extremity before being followed up by trunk.…”
Section: Discussionmentioning
confidence: 99%
“…10 It was previously shown that unstable turn might follow up to unstable gait, being unable to walk in a straight line as the subject tries to restore their balance following the pivot turn. 9,10 In an extensive observation of turns, it was shown that young subjects with no difficulty of turning that none would initiate their turn with forward leaning, it would either be vertically aligned trunk and hip, slight backward lean, or initiated by lower extremity before being followed up by trunk. 9 The three steps turning method effectively adapt this physiologic trajectory of turning, hence reflecting adequate motor control, and leading to better quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However in cases of SCA, probably the complete TUG test might not always be performable due to high risk of fall. Several studies had also utilized expanded TUG test, which divides the full TUG test into segments measured by milliseconds, namely sit to stand, gait 1, turning, gait 2, and stand to sit [48,49]. By separating these components, physiatrists would have a better view on which component are hindering the subject in achieving good TUG performance, and at the same time, would be able to assess improvements more accurately.…”
Section: Functional Measurement Toolsmentioning
confidence: 99%
“…By separating these components, physiatrists would have a better view on which component are hindering the subject in achieving good TUG performance, and at the same time, would be able to assess improvements more accurately. Although the expanded TUG have not been utilized in SCA studies, it has been commonly used in other chronic neurological cases such as stroke, and hence should be recommended for future studies on degenerative ataxia [48].…”
Section: Functional Measurement Toolsmentioning
confidence: 99%